The Effect of Geographical Education in Improving The Character of Educational Insights Students: A Study of Geographical Education - Amin Amin; Hermanto Hermanto (Jurnal Basicedu, 2022)
This study intends to examine three elements: first, how students care about the environment; second, the function of geography education in creating environmental awareness in students; and third, how sociocultural, psychological, and demographic factors affect students' spiritual intelligence. A sample of 79 students from SMP YPI “45” Bekasi participated in this survey. Through the use of questionnaires, data collection procedures were used, and SPSS software was used to analyze the results. Students' assessment of the geography instructor's ability to integrate current environmental issues into their lessons, as well as the student's socio-economic origins and involvement in environmental groups, all have an impact on the student's environmental caring character. An area of interest of study is how socio-economic and cultural features and Demographics affect the ecoliteracy of students and how geography education contributes to the development of their ecoliteracy as a result.